2013
DOI: 10.1038/sc.2013.78
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ankle joint mobility when using an orthosis on stability in patients with spinal cord injury: a pilot study

Abstract: Objectives: Perceived risk of falling is an important factor for people with spinal cord injury (SCI). This study investigated the influence of ankle joint motion on postural stability and walking in people with SCI when using an orthosis. Methods: Volunteer subjects with SCI (n ¼ 5) participated in this study. Each subject was fitted with an advanced reciprocating gait orthosis (ARGO) equipped with either solid or dorsiflexion-assist type ankle-foot orthosis (AFOs) and walked at their self-selected speed alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…As the reach was in the anterior-posterior direction, we assume that AFO flexible gauntlet design did not restrict forward reach, but improved the ankle hip co-ordination. Similar results of improved postural stability and walking (Arazpour et al, 2013;Menotti et al, 2014) were found in other older adult populations as well when using a flexible AFO design.…”
Section: Discussionsupporting
confidence: 87%
“…As the reach was in the anterior-posterior direction, we assume that AFO flexible gauntlet design did not restrict forward reach, but improved the ankle hip co-ordination. Similar results of improved postural stability and walking (Arazpour et al, 2013;Menotti et al, 2014) were found in other older adult populations as well when using a flexible AFO design.…”
Section: Discussionsupporting
confidence: 87%
“…29 Also, in using a AFO, Arazpour et al demonstrated that using an ARGO with dorsiflexion-assisted AFOs increased the fear of falling, but did improve static postural stability and increased walking speed and endurance. 18 Increase of temporal spatial parameters and Figure 1. IRGO overall view and dorsiflexion-assisted ankle joints used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The 1 use of reciprocal gait orthoses (RGOs) when utilizing dorsiflexionassisted AFOs to walk has a potential to decrease the energy consumption based on increased endurance compared with those with solid AFOs. 18 However, the effect of ankle joint mobility on energy consumption is not clear in SCI patients. Based on the important role of the ankle joint during walking and improvement of walking parameters via movable ankle joints in using mechanical orthosis, we hypothesized that ankle joint mobility would have a positive effect on reducing energy consumption during walking with an IRGO.…”
Section: Introductionmentioning
confidence: 99%
“…Orthotic training in SCI subjects can be reduced fatigue and fear of falling and increased the stepping [61]. It was announced that after training program, SCI subjects had walking ability and performance of activity of daily living.…”
Section: Orthotic Gait Training Protocolmentioning
confidence: 99%